2011
DOI: 10.3797/scipharm.1106-18
|View full text |Cite
|
Sign up to set email alerts
|

Study on Cytochrome P-450 Dependent Retinoic Acid Metabolism and its Inhibitors As Potential Agents for Cancer Therapy

Abstract: The relative lack of clinical success with conventional anticancer agents may be due in part to the traditional concept of cancer being a biological state rather than a dynamic process. Redefining cancer as a dynamic disease commencing with carcinogenesis introduces the possibility of chemoprevention. Retinoids offer the promise of a therapeutic option based on differentiation of premalignant as well as malignant cells. Research to date has concentrated on the use of exogenous retinoids in cancer. Although thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In addition, they have been shown to suppress carcinogenesis in a variety of tumor types and have demonstrated success for the treatment and chemoprevention of human cancers (Freemantle, Spinella, & Dmitrovsky, 2003). Despite these encouraging results, the effects of prolonged retinoid therapy on human cancers in the clinic has been scarce and disappointing (Ahmad, 2011). It has been suggested that the therapeutic effects of retinoids such as all-trans retinoic acid (ATRA) are undermined by its rapid in vivo metabolism and catabolism by cytochrome P450 enzymes (Ahmad, 2011;Marill, Idres, Capron, Nguyen, & Chabot, 2003;Njar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they have been shown to suppress carcinogenesis in a variety of tumor types and have demonstrated success for the treatment and chemoprevention of human cancers (Freemantle, Spinella, & Dmitrovsky, 2003). Despite these encouraging results, the effects of prolonged retinoid therapy on human cancers in the clinic has been scarce and disappointing (Ahmad, 2011). It has been suggested that the therapeutic effects of retinoids such as all-trans retinoic acid (ATRA) are undermined by its rapid in vivo metabolism and catabolism by cytochrome P450 enzymes (Ahmad, 2011;Marill, Idres, Capron, Nguyen, & Chabot, 2003;Njar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these encouraging results, the effects of prolonged retinoid therapy on human cancers in the clinic has been scarce and disappointing (Ahmad, 2011). It has been suggested that the therapeutic effects of retinoids such as all-trans retinoic acid (ATRA) are undermined by its rapid in vivo metabolism and catabolism by cytochrome P450 enzymes (Ahmad, 2011;Marill, Idres, Capron, Nguyen, & Chabot, 2003;Njar et al, 2006). In addition, side effects constitute a limit to the chronic use of these systemic agents (Saurat, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…While there have not been clinical trials with itraconazole or voriconazole as inhibitors of RA metabolism, there are several case reports of these compounds resulting in hypervitaminosis A symptoms, particularly in patients receiving exogenous RA [144148]. Furthermore, there is in vitro evidence of these compounds inhibiting RA metabolism, although they are not particularly potent [27, 155]. Thus, while these compounds are capable of inhibiting RA metabolism, they have not been pursued for this purpose, most likely because of their lack of specificity and their weak inhibition of CYP26A1.…”
Section: Pharmacological Effects Of Inhibitors Of Retinoic Acid Hymentioning
confidence: 99%
“…The metabolism of retinoids by hepatic hydroxylation involves multiple CYP450 enzymes including CYP3A4 (52,53). In vitro studies have demonstrated an 85% decrease in retinoid metabolism with coadministrated chlorpromazine and 87% decrease with ketoconazole (52).…”
Section: Retinoidsmentioning
confidence: 99%
“…The metabolism of retinoids by hepatic hydroxylation involves multiple CYP450 enzymes including CYP3A4 (52,53). In vitro studies have demonstrated an 85% decrease in retinoid metabolism with coadministrated chlorpromazine and 87% decrease with ketoconazole (52). A more recent clinical study with 54 participants showed no clinical significance of CYP3A4 interactions with ketoconazole, simvastatin, and cyclosporine (53).…”
Section: Retinoidsmentioning
confidence: 99%